Geochemistry and geochronology of Carboniferous volcanic rocks from the Edren range, Trans-Altai Zone, SW Mongolia - Javkhlan, Otgonkhuu; Chimedtseren, Anaad; Gerel, Ochir; Bayaraa, Batkhishig; Munkhtsengel, Baatar (Mongolian Geoscientist, 2022)
The Edren range of the Trans-Altai zone is situated in the central south part of the Central Asian Orogenic Belt. The Edren range is composed primarily of volcano-sedimentary rocks that were weakly metamorphosed during the Devonian to Carboniferous periods. These rocks were then intruded by granite plutons during the Carboniferous to Permian periods. The area is further divided into two units, the Edrengiin Nuruu and Davkhar Khar, which are separated by the Khyariingun thrust fault. Three episodes of magmatism have been recognized in the Edren range. The earliest episode of magmatism at c. 360 Ma is present in the Edrengiin Nuruu unit. A younger episode of magmatism at c. 330 Ma is present in the Davkhar Khar unit. The youngest episode of magmatism, dated at c. 300 Ma is represented by rhyolite porphyry dykes in the Edrengiin Nuruu unit. The first episode of c. 360 Ma volcanism, developed in a continental arc setting, produced relatively contaminated basalt-andesite magma (SiO2=49.39-57.65 wt%; Mg#=27-47; (La/Yb)N=3.24-15.39) with relatively low initial ɛNd-values (from ca. +1.9 to +4.3) by subduction of the oceanic crust, developed on Devonian continental juvenile crust. Following subduction, steady northward transition of volcanic arc occurred. At c. 330 Ma continuous subduction of oceanic crust produced basalt-andesite-rhyolite magma (SiO2=47.16-72.76 wt%; Mg#=4-48; (La/Yb)N=1.34-10.91) with higher initial ɛNd-values (from ca. +1.6 to +5.8). At c. 300 Ma, rhyolite porphyry dykes (SiO2=75.70-75.86 wt%; Mg#=5-6; ɛNd=+2.6) developed in the Edrengiin Nuruu unit by subduction or collision-related magmatism.